5-Hydroxy-1, 4-naphthalenedione exerts anticancer effects on glioma cells through interaction with the mitochondrial electron transport chain. (3rd February 2017) - Sidlauskas, Kastytis; Sidlauskiene, Ruta; Li, Ningning; Liobikas, Julius
Highlights: 5-Hydroxy-1, 4-naphthalenedione (juglone) exerts anticancer effects on glioma cells. Juglone is selective to gliomas cells as compared to the isolated glial culture. The anticancer effect of juglone depends on excess production of intracellular ROS. The ROS generation is partly mediated through interaction with the complex I. Abstract: Survival of patients with glioblastoma remains within the range of several months despite advances in therapeutic options. We have already shown that 5-hydroxy-1, 4-naphthalenedione (juglone) exerts antiproliferative, anti-invasive, and cytotoxic effects on glioma C6 cells. Here, we further revealed that juglone is relatively selective to glioma cells as compared to the normal glial culture, and investigated its mechanisms of action. The incubation of glioma C6 cells with juglone generated high levels of reactive oxygen species (ROS). The produced ROS accounted for the anticancer effect of juglone as antioxidant N -acetylcysteine reduced both cytotoxic and antiproliferative activities of juglone. Furthermore, high resolution respirometry revealed that juglone decreased oxygen consumption mainly by affecting pyruvate/malate- and glutamate/malate-induced mitochondrial respiration. The inhibition of respiratory complex I by amytal decreased juglone-triggered generation of ROS and diminished its anticancer activity. Thus, our results indicate that juglone generates ROS through interaction with respiratory complex I in glioma C6 cells, and, in turn, induces the anticancer effects.